Separation Of Phenylarsonic Compounds By Ion Pairing-Reversed Phase-High Performance Liquid Chromatography - Jaafar, Jafariah (Penerbit UTM Press, 2001)
Phenylarsonic compounds are extensively used as feed additives to promote growth and to control disease in the poultry industry. A method was conducted that allowed the analysis of arsenic animal feed additives by ion pairing-reversed phase HPLC (IP-RP-HPLC) with a UV detection using an octadecylsilylsilica column. The separation of anionic arsenic compounds [3-nitro-4-hydroxyphenylarsonic acid (3-NHPAA), p-arsanilic acid (p-ASA) and phenylarsonic acid (PA)] was accomplished using 5 mM tetrabutylammonium chloride as the ion pairing reagent in aqueous mobile phase containing 3 mM malonic acid and 5% methanol at a flow rate of 1.4 mL min–1. The influence of mobile phase pH on the separation was studied; the optimum pH found was 5.85. The detection limit obtained for 3-NHPAA was 0.43 ng As.